On Analysing Changes in Urban Form - Some Theoretical and Methodological Issues - Marcus Adolphson; Folke Snickars (European Regional Science Association (ERSA), 2003)
The urban structure is a result of human actions and affects its users in a cyclic relationship. The political systems on different levels put attention to the urban structure and its relationship to the ecological and sociological and economical systems. This attention is expressed on the European level, for instance, in the European Spatial Development Perspective (ESDP) where a spatial structure according to the polycentric urban system principle is recommended. The first aim of this study is to discuss spatial location factors for the temporal and geographical development of urban residential structures. The second aim of the study is to investigate the relative importance of the discussed location factors using a segment of a Swedish county as a test case. The basic question is whether the location of new residential areas is determined through market forces or political decisions. Thus, the paper addresses the fundamental question of the efficiency of land-use planning decisions. By geo-coding existing geographical real estate tax databases and combining the information with existing digital maps and satellite images the spatial development over time will be analysed in a geographic information system. By non-parametric statistical tests and multiple regression analyses the importance of individual factors relative to one another will be determined. The analysis is performed at as low a geographical level as possible. If the urban development exhibits some regularity, and hence is not totally random with the regards to the explanatory factors in question, then is it possible to investigate the development as a system of spatial causalities. The study is based on earlier investigations by, among others, Rietveld & Wagtendonk (2000), Filion, Bunting & Warriner (1999) and de la Barra (1989). However, the current investigation will use disaggregated geographical data on micro level with a high spatial resolution. The case study is performed in an area affected by high speed commuting train from the middle of the analysis period 1980-2000, which calls for also a detailed representation of the transport system. References: Rietveld P & Wagtendonk AJ (2000), The location of new residential areas in the Netherlands: A statistical analysis for the period between 1980 and 1995, Paper presented to the 40th congress of the European Regional Science Association (2000), Barcelona, Spain. Filion P., Bunting T. och Warriner K. (1999). The entrenchment of urban dispersion: Residental preferences and location patterns in the dispersed city. Urban Studies, 36, (8), 1317-1347. de la Barra T. (1989). Integrated land use and transport modelling: decision chains and hierarchies. New York. Cambridge university press.
Keywords: 330